H-Bonding-mediated binding and charge reorganization of proteins on gold nanoparticles. Issue 8 (18th February 2020) - Meesaragandla, Brahmaiah; García, Isabel; Biedenweg, Doreen; Toro-Mendoza, Jhoan; Coluzza, Ivan; Liz-Marzán, Luis M.; Delcea, Mihaela
Abstract : Gold nanoparticles with various functionalities interact with the human serum albumin (HSA) leading to protein structural changes. HSA-nanoparticles bioconjugates display lower toxicity and slower cell uptake rates, compared to nanoparticles in the absence of protein. Abstract : Once introduced into the human body, nanoparticles often interact with blood proteins, which in turn undergo structural changes upon adsorption. Although protein corona formation is a widely studied phenomenon, the structure of proteins adsorbed on nanoparticles is far less understood. We propose a model to describe the interaction between human serum albumin (HSA) and nanoparticles (NPs) with arbitrary coatings. Our model takes into account the competition between protonated and unprotonated polymer ends and the curvature of the NPs. To this end, we explored the effects of surface ligands (citrate, PEG-OMe, PEG-NH2, PEG-COOH, and glycan) on gold nanoparticles (AuNPs) and the pH of the medium on structural changes in the most abundant protein in blood plasma (HSA), as well as the impact of such changes on cytotoxicity and cellular uptake. We observed a counterintuitive effect on the ζ -potential upon binding of negatively charged HSA, while circular dichroism spectroscopy at various pH values showed an unexpected pattern in the reduction of α-helix content, as a function of surface chemistry and curvature. Our model qualitatively reproduces the decrease in α-helix content, thereby offering a rationale based on particle curvature. The simulations quantitatively reproduce the charge inversion measured experimentally through the ζ -potential of the AuNPs in the presence of HSA. Finally, we found that AuNPs with adsorbed HSA display lower toxicity and slower cell uptake rates, compared to functionalized systems in the absence of protein. Our study allows examining and explaining the conformational dynamics of blood proteins triggered by NPs and corona formation, thereby opening new avenues toward designing safer NPs for drug delivery and nanomedical applications.